THE ROLE OF CUSTOMER SATISFACTION IN INCREASING CUSTOMER LOYALTY - Siswi, Ati Arifiah; Wahyono, Wahyono (Universitas Negeri Semarang, 2020)
The purpose of this study is to determine the direct and indirect influence of brand personality, brand reputation and price fairness toward customer loyalty through customer satisfaction as an intervening variable. Customer satisfaction influence customers to make an loyal. The population in this research is customers Kukubima Energi. The total sample in this research is 115 respondents with purposive sampling technique through a likert scale. Methods of collecting data using questionnaires and documentation. Data analysis using classic assumption test and hypothesis test (t test and path analysis) with SPSS Statistics version 21 programs. Based on the hypothesis test, the results show that brand personality has a positive and significant effect on customer loyalty, price fairness has a positive and significant effect on customer loyalty, brand reputation does not has a positive and significant effect on customer loyalty, and customer satisfaction has a positive and significant effect customer satisfaction. Mediation test shows that positive emotion mediates the effect of brand personality, and price fairness on customer satisfaction.